THE EFFECTIVENESS OF DEVELOPING SCIENCE E-MODULES BASED PROJECT-BASED LEARNING TO IMPROVE THE COMMUNICATION SKILLS OF GRADE 5th STUDENTS - Asriani Asriani; Retno Triwoelandari; Hambari (Universitas Majalengka, 2023)
21st century teachers are required to be able to integrate information and communication technology (ICT) in the learning process. In addition, teachers must be able to equip students with skills needed in the 21st century, one of which is communication skills. Science as a subject studied since elementary school is related to communication skills. Therefore, this study aims to develop a project-based learning science learning e-module to improve the communication skills of grade 5 elementary school/ MI students. In addition, this study is focused on knowing the development process, feasibility and effectiveness in improving students' communication skills. The development of the e-module is carried out using the Research and Development (R&D) 4D model and data collection was carried out through interviews, observations and questionnaires. Meanwhile, data analysis was carried out by measuring the validity of the e-module by material experts, linguists and media experts while to determine the effectiveness of normality, homogeneity and hypothesis tests of independent samples t-test. Based on the overall feasibility test results, a score of 81.9% was obtained, which means that the e-modules that have been developed are very valid and suitable for use in science learning. In addition, the effectiveness test was carried out using the SPSS FOR Windows 26 application from posttest and pretest data in the control class and experimental class, obtained Sig. (2-Tailed) results of 0.001 or less than 0.05 which means there is a significant difference. Thus, it can be concluded that the project-based learning e-module of science learning is declared effective for improving students' communication skills. Keywords: Effectiveness, Development, E-module, Communication Skills. Guru abad 21 didituntut untuk mampu mengintegrasikan teknologi informasi dan komunikasi (TIK) dalam proses pembelajaran. Selain itu, guru harus mampu membekali siswa dengan keterampilan yang dibutuhkan di abad 21, salah satunya keterampilan komunikasi. IPA sebagai mata pelajaran yang dipelajari sejak SD berkaitan dengan keterampilan komunikasi. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan e-modul pembelajaran IPA berbasis project based learning untuk meningkatkan keterampilan komunikasi siswa kelas 5 SD/MI. Selain itu, penelitian ini difokuskan untuk mengetahui proses pengembangan, kelayakan dan keefektifannya dalam meningkatkan keterampilan komunikasi siswa. Pengembangan e-modul dilakukan menggunakan metode Research and Development (R&D) model 4D dan pengumpulan data dilakukan melalui wawancara, observasi serta angket. Adapun, analisis data dilakukan dengan mengukur validitas e-modul oleh ahli materi, ahli bahasa dan ahli media sedangkan untuk mengetahui efektivitas dilakukan uji normalitas, homogenitas dan uji hipotesis independent samples t-test. Berdasarkan hasil uji kelayakan secara keseluruhan diperoleh skor 81,9% yang berarti e-modul yang telah dikembangkan sangat valid dan layak digunakan dalam pembelajaran IPA. Selain itu, uji efektivitas dilakukan dengan menggunakan aplikasi SPSS FOR Windows 26 dari data posttest dan pretest di kelas kontrol dan kelas eksperimen, didapatkan hasil Sig.(2-Tailed) 0,001 atau kurang dari 0,05 yang berarti terdapat perbedaan yang signifikan. Dengan demikian, dapat disimpulkan bahwa e-modul pembelajaran IPA berbasis project based learning dinyatakan efektif untuk meningkatkan keterampilan komunikasi siswa.